Rancang Bangun Sistem Informasi Perusahaan untuk Mendukung Rekrutmen Karyawan Pada PT.Isargas - Khaidir Fahram (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2021)
A company certainly needs fast and accurate information, one of which is information about employee recruitment. PT Isargas is a private company engaged in the transmission and distribution of natural gas. Currently, the employee recruitment process is still very manual, by coming directly to the company to see a board that contains information on available job vacancies. And data processing using Ms. application. Excel. Which requires a lot of time and money. In this case the authors conducted several studies on the company using several methods including using data collection methods, analysis methods, system design methods, and testing methods. Where the data collection methods are in the form of observations, interviews, literature studies such as observation, asking sources and searching for books. The analysis method used includes SWOT analysis, system design methods where the writing of the system uses UML (Unified Modeling Language), and the testing method uses blackbox testing. In this case the researcher has several objectives in conducting this research, including being able to find out which system is currently running in the company, minimizing errors that often occur due to the use of manual systems, and designing a recruitment system from manual to system, so that in this study it produces benefits such as providing solutions regarding the need for information systems in decision making that can run smoothly and accurately, facilitate the decision-making process regarding employee recruitment, and produce a web-based employee recruitment system.